Do Neighborhoods Affect the Credit Market Decisions of Low-Income Borrowers? Evidence from the Moving to Opportunity Experiment - Miller, Sarah; Soo, Cindy K (Review of Financial Studies, 2021)
Abstract This paper isolates the causal impact of neighborhood environment on the credit outcomes of low-income borrowers by analyzing the participants of the Moving to Opportunity (MTO) experiment. MTO was a unique, large-scale experiment that offered families vouchers to move to better neighborhoods via randomized lottery. We find higher credit scores and use among those required to move to the lowest poverty areas as young children. For those who moved as adults, we find that better neighborhoods lead to a reduction of overdue debts and delinquencies, but only among those given unrestricted neighborhood choice.